Performance Optimization of an eCAR by Parametric Analysis - Gururaj, G.; Gowri, K. S. (Engineering, Technology & Applied Science Research, 2019)
In this paper, a method for performance optimization of an electric Car (eCAR) is proposed based on acceleration rate, maximum speed, and tractive force. Since the total tractive force is exerted by propulsion motor alone, the driving performance of an eCAR depends on the power of the propulsion motor and its control. The proposed pre-sizing methodology depicts the optimum power of the propulsion motor, and for the optimized motor the impact of road dynamics, acceleration rate, change in mass, and gear ratio on the eCAR’s drive range are analyzed. The proposed electric propulsion system is modeled and the performance characteristics are analyzed using MATLAB to validate the behavior of an eCAR propulsion.